Evaluating the Population Dynamics of Leptualaca fassicollis Thoms (Coleoptera: Chrysomelidae) and Megalurothrips usitatus Bagnall (Thysanoptera: Thripide) on Pigeonpea under the Influence of Plant Density and Planting Date in a Rain Forest Zone, Nigeria - Dialoke S. A; Enujeke E.C; Awere S.U; Uluocha O.B; Azubuike N.O.; Umelo C.Q (Current Research Progress in Agricultural Sciences Vol. 8, 2025)
In Nigeria, mainly in the rainforest zone of South Eastern Nigeria, there is limited information on the appropriate time to plant early maturing pigeonpea cultivars, and studies are limited on both the production and insect pest problems associated with the improved pigeonpea. Therefore, this research was carried out to determine the best plant density and date of planting early maturing pigeonpea (ICPL 84023) in relation to L. fassicollis and flower thrips infestation for optimum performance in the field. The study was carried out in the months of April, July, and October 2009 and repeated in 2010 in the Postgraduate Teaching and Research Farms, Imo State Nigeria. Experiment was laid out in a 3 x 4 factorial and treatments consisted of four plant populations with density of 190,474 plants ha-1 (15 cm x 35 cm), 125,000 plants ha-1 (20 cm x 40 cm), 80,000 plants ha-1 (25 cm x 50 cm), 55,556 plants ha-1 (30 cm x 60 cm), with three planting dates, April (early season), July (Mid-season), and October (late season), 2009 and 2010. The result of the effects of plant densities and planting dates on the population of pigeonpea Leptualaca fassicollis thoms and Megalurothrips usitatus Bagnall showed that pigeonpea planted at a higher plant density of 190,474 plants ha-1 had a higher population of L. fassicollis and flower thrips compared with pigeonpea plants at lower densities. Thus, a relationship between cultivation techniques (using lower plant densities) and planting schedule (planting during July) with respect to the abundance of pests population can have a commendable effect in advancing Integrated Pest Management (IPM) strategies and fostering climate-resilient agricultural practices in pigeon pea production.